2015
DOI: 10.1098/rstb.2014.0295
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between multiple helminths and the gut microbiota in wild rodents

Abstract: The gut microbiota is vital to host health and, as such, it is important to elucidate the mechanisms altering its composition and diversity. Intestinal helminths are host immunomodulators and have evolved both temporally and spatially in close association with the gut microbiota, resulting in potential mechanistic interplay. Host–helminth and host–microbiota interactions are comparatively well-examined, unlike microbiota–helminth relationships, which typically focus on experimental infection with a single helm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
182
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(200 citation statements)
references
References 59 publications
13
182
3
2
Order By: Relevance
“…This family is commonly found in rats, mice, goats, and humans and has also been correlated with a highfat diet, immunoglobin A, tapeworms, etc. Thus, the S24-7 family may generally be sensitive to dietary shifts (50)(51)(52)(53)(54). Given the widespread distribution of this family and correlation with a number of dietary components, S24-7 represents a significant gap in our understanding of the gut microbiota form and function.…”
Section: Discussionmentioning
confidence: 99%
“…This family is commonly found in rats, mice, goats, and humans and has also been correlated with a highfat diet, immunoglobin A, tapeworms, etc. Thus, the S24-7 family may generally be sensitive to dietary shifts (50)(51)(52)(53)(54). Given the widespread distribution of this family and correlation with a number of dietary components, S24-7 represents a significant gap in our understanding of the gut microbiota form and function.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, intestinal helminths and protozoa may cause reduced energy uptake, pathological damage and decrease their hosts' reproductive success (Hudson et al, 1992(Hudson et al, , 1998Delahay et al, 1995;Hillegass et al, 2010). In addition, they impact the host's immune system and alter gut microbial communities (Kreisinger et al, 2015;Reynolds et al, 2015), potentially increasing host susceptibility to bacteria or viruses (Cox, 2001;Ezenwa and Jolles, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This increases the bacterial density in the gut with helminths, as food is retained for a longer time allowing the bacteria to act on it [8]. Kreisinger et al [9] also gave valuable inputs in this field by demonstrating alteration of the host gut microbiota depending on the species of helminth present in the gut. The study also revealed that the helminths could regulate the microbial communities both upstream and downstream of their location using H. polygyrus, Syphacia spp.…”
Section: Effects Of the Presence Of Helminths On Gut-microbiota Shiftmentioning
confidence: 99%
“…and Hymenolepis spp in their experiments [9]. The results throw light to the potentiality of the helminths to alter the gut homeostasis [9]. The ability of the helmnith to regulate the gut microbial population, not necessarily directly on their location and/or depending on the species of helminth in question is very interesting since different species of helminths (alone or in combination) may be used to study such microbial regulation from the therapeutic viewpoint both for the humans and the veterinary animals.…”
Section: Effects Of the Presence Of Helminths On Gut-microbiota Shiftmentioning
confidence: 99%
See 1 more Smart Citation